Appetite in captivity - feeding studies of the red sea cucumber Parastichopus tremulus - Sunde, Jan; Christophersen, Gyda (Frontiers in Marine Science, 2023)
The deposit feeding sea cucumber Parastichopus tremulus is an underutilised resource in North Atlantic waters. Geographically it is distributed from the Barents Sea in the north to the Canary Islands in the south. At present performance of P. tremulus in aquaculture is largely unknown. Species and stage specific biological knowledge gaps need to be filled for a potential industry to develop, and feeds that support growth needs special attention. Particulate matter (sludge) from fish farms is an unutilised resource that has potential as ingredient in feeds for sea cucumbers, which would help to reduce the environmental footprint of P. tremulus aquaculture production. The suitability of salmon sludge as a feed ingredient is unknown. Feeds using dried salmon freshwater sludge (50% and 75% volume ratios) or seaweed powder (Sargassum spp. 25%, 50% and 75% volume ratios) were compared in this study. Feed mixes with different ratios of ingredients and sand (0.6-1 mm) were given in excess (50% wet weight/wet weight animal/week) to adult P. tremulus. Daily feed intake was estimated by measuring daily faeces production rate. Each animal was given all feeds sequentially, and faeces collected for a ten-day period. Absorption efficiencies were estimated based on analysis of organic matter content in feed and faeces. Large variations were found in feed intake, both between individuals and between days. Our results indicated that P. tremulus showed a higher intake of feeds containing seaweed, with a trend of higher intake with increasing seaweed content. Absorption efficiency estimates of seaweed-based feeds ranged from -337 to 73.7%. P. tremulus showed a preferential selection of organic particles in the feed with lowest content of seaweed. Absorption efficiency of feeds containing sludge (2.5 – 58.3%) was comparable to that of feeds containing seaweed, however, feed intake of sludge-based feeds was significantly lower than that of the seaweed-based feeds and resulted in large variation in estimates. The results suggest that salmon freshwater sludge could have a potential future use as an ingredient in sustainable feeds for P. tremulus, but that optimisation of feed formulations need to be studied further.